2022
DOI: 10.3390/ijerph191711131
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Sustainable Operations with Sustainable Supply Chain Modeling: A Case of Organizational Culture and Normative Commitment

Abstract: The importance of sustainability in supply chain management is growing worldwide. It is possible to find reasons for this using various phenomena that negatively affect humanity, e.g., climate change, scarce materials, supply disruptions, and complex fossil fuel dependency. Because of that, is extremely important to constantly look for new ways to systematically increase sustainability in enterprises and their logistics and supply chain processes by considering different stakeholders and influential factors. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 103 publications
0
1
0
Order By: Relevance
“…The rows and columns of the matrix are the individual potential causes of non-compliance and the corresponding values of the degree of impact of these causes. The pairwise comparison of the degree of influence of the causes of nonconformity is to calculate the difference between the mutual influences of these causes, as in Formula (5).…”
Section: Step 4 Identification Of Causes Of Potential Non-compliancementioning
confidence: 99%
See 1 more Smart Citation
“…The rows and columns of the matrix are the individual potential causes of non-compliance and the corresponding values of the degree of impact of these causes. The pairwise comparison of the degree of influence of the causes of nonconformity is to calculate the difference between the mutual influences of these causes, as in Formula (5).…”
Section: Step 4 Identification Of Causes Of Potential Non-compliancementioning
confidence: 99%
“…It is still difficult to ensure the repeatability of the results under industrial conditions, mainly as part of special material processes [ 1 , 2 ]. It refers to the processing and production of products compatible with quality [ 3 , 4 ], in order for special processes to be realised based on the validated algorithm or method [ 5 , 6 ]. The companies are taking different actions in this area [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…After the literature review, it was shown that analyses of using RES (mainly PV) were performed considering that the expectations were realized, for example, [24][25][26]. They were based, for example, on efficiency, price, or application possibilities [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Industrial development could be described as structurally unsustainable, resource-intensive, extensive, and inefficient [1,2]. A significant number of environmental problems have not been solved, degradation of the natural environment has continued, and the ecological crisis has intensified [3,4]. The numerous ecological and social threats occurring in the world influenced preventive measures of global scope; this in turn resulted in the development of the assumptions of the idea of sustainable development [5,6].…”
Section: Introductionmentioning
confidence: 99%